NON-ISLET CELL TUMOR HYPOGLYCAEMIA IN A FRAIL ELDERLY PATIENT: A CASE REPORT - Marzukie, Marisa Masera; Chia, Wei Zhi; Salleh, Mohd Fauzan; Chai, Shu Teng; Teoh, Jamie Hong Im; Ali, Norhaliza Mohd (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Non-islet cell tumor hypoglycemia (NICTH) is a rare paraneoplastic phenomenon, representing the second most common aetiology of spontaneous hypoglycemia in nondiabetic patients after insulinoma. It is seen in patients with extra-pancreatic tumors, usually of mesenchymal, vascular, or epithelial origin. The underlying mechanism involves tumor over secretion of incompletely processed insulinlike growth factor-2 (pro-IGF-2), leading to the activation of insulin receptors and thereby hypoinsulinaemic hypoglycaemia. We report an elderly female, who presented with recurrent spontaneous hypoglycaemia, following which subsequent workup confirmed the diagnosis of NICTH secondary to a left lung mitotic lesion. CASE An 86-year-old, non-diabetic female presented with early morning spontaneous hypoglycaemia of two years’ duration. She was found by her family confused and was only able to regain full consciousness after taking sweet beverages or nutritional drinks. Her documented capillary blood glucose levels during these episodes confirmed that she had hypoglycemia. She denied weight change and altered bowel habits. She had a strong family history of malignancy, wherein five of her eight children had colorectal carcinoma. Supervised fasting test showed low C-peptide, undetectable serum insulin and low blood ketone when the concurrent blood glucose level was 1.1 mmol/L. Following glucagon challenge, her blood glucose rose to 3.3 mmol/L. Sulphonylurea screen was negative. Serum IGF-2 was not tested due to unavailability. A diagnosis of NICTH was made. CECT thorax revealed a large left lower lobe lung tumour, measuring 11.5 x 8.9 x 12.9 cm, which partially encased the left main bronchus and descending thoracic aorta. Due to her advanced age, she refused biopsy and surgery. Her hypoglycaemia was treated with raw cornstarch therapy before bed and at 3 am, as well as oral prednisolone 5 mg daily. CONCLUSION The possibility of NICTH should be considered in the evaluation of spontaneous hypoglycemia in an elderly non-diabetic patient. Glucocorticoids can be effective in ameliorating hypoglycemia in this setting when surgery is not feasible.